2021
DOI: 10.1093/rap/rkab059
|View full text |Cite
|
Sign up to set email alerts
|

Role of the halo sign in the assessment of giant cell arteritis: a systematic review and meta-analysis

Abstract: Objectives This systematic review and meta-analysis aimed to evaluate the diagnostic value of the halo sign in the assessment of GCA. Methods A systematic literature review was performed using MEDLINE, EMBASE and Cochrane central register databases up to August 2020. Studies informing on the sensitivity and specificity of the US halo sign for GCA (index test) were selected. Studies with a minimum of five participants were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
4
14
2
Order By: Relevance
“…Characteristic US TA halo signs and the TA intima–media thickness showed a significant differentiation between the TAB-positive GCA patients and the TAB-negative GCA patients. Overall, our results regarding the US-measured TA vessel-wall thicknesses aligned well with the results of a large multicentric study entitled “The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis” (TABUL) [ 17 ], a recent meta-analysis [ 31 ], and a diagnostic performance utility study on the thickness of the intima–media complex [ 32 ]. In these studies, a cut-off value of intima–media thickness was determined at 0.4 mm for GCA diagnosis based on US measurement.…”
Section: Discussionsupporting
confidence: 78%
“…Characteristic US TA halo signs and the TA intima–media thickness showed a significant differentiation between the TAB-positive GCA patients and the TAB-negative GCA patients. Overall, our results regarding the US-measured TA vessel-wall thicknesses aligned well with the results of a large multicentric study entitled “The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis” (TABUL) [ 17 ], a recent meta-analysis [ 31 ], and a diagnostic performance utility study on the thickness of the intima–media complex [ 32 ]. In these studies, a cut-off value of intima–media thickness was determined at 0.4 mm for GCA diagnosis based on US measurement.…”
Section: Discussionsupporting
confidence: 78%
“…These changes were observed throughout the collected samples. A recent systematic review showed that, in the setting of GCA, the specificity of the appearance of halo sign on ultrasound is as high as 95% (95% confidence interval 89–98%) when the clinical diagnosis is used as a reference (1); however, this is especially true in the acute phase (2) and not in all phases (e.g., in the late phase as in the present case). Thus, in addition to ultrasound, a comprehensive examination, especially at the time of symptom onset, should be considered for the accurate diagnosis of GCA.…”
mentioning
confidence: 60%
“…Local increase in blood flow velocities in the intracranial arteries and/or decreased pulsatility and/or resistance indices as a sign of migraine [79][80][81] Local increase in blood flow velocities in the intracranial arteries as a sign of reversible cerebral vasoconstriction syndrome, vasospasm [31,32] Arterial dissection [5,27,62] Local increase in blood flow velocities in the intracranial arteries and/or increased pulsatility and/or resistance indices as a sign of neuroinfection/vasculitis (meningitis, encephalitis) [9,14,24,59,77,78] Giant cell arteritis with halo sign [82] 4.…”
Section: Headachementioning
confidence: 99%